Compare and Analysis of Cylindrical Rolling Element Bearing Surface Cracks Nature - Xu Jian (Jixie chuandong)
A rolling surface crack of the cylindrical roller bearings used in an aeroengine fulcrum is found after work,the material for rolling elements is W9Cr4V2 Mo. Through the morphology observation,energy spectrum analysis and metallographic analysis of the rolling surface morphology crack,and the test results are compared with the material for M50 and GCr15 of cylindrical roller bearing surface crack,it is obtained that the material surface cracks of W9Cr4V2 Mo rolling body is produced in the process of rolling the rod used in the cold-drawn molding process,the crack nature is forging folding defects.